Long-term effect of whole tree biomass harvesting on ground cover vegetation in a dry Scots pine stand - Jansons, Āris; Robalte, Linda; Čakšs, Roberts; Matisons, Roberts (Silva Fennica, 2016)
Long-term (47 years) effect of experimental whole tree harvesting (WTH) with a heavy soil scarification on ground cover vegetation was assessed in a dry nutrient-poor Scots pine ( L.) stand in Latvia. Neighbouring conventionally managed young (10 years) and mature (119 years) stands of the same type were used for comparison. Higher species richness was observed in the WTH stand compared to conventionally managed young and mature stands (24, 18 and 16 species, respectively), likely due to the profound disturbance. The Shannon diversity index was higher in the young than in the WTH and mature stands (2.36, 1.77 and 1.63, respectively); still, the composition and structure of ground cover vegetation in WTH was more similar to the mature stand. Nevertheless, the occurrence of oligotrophic species in the WTH stand suggested decreased soil nutrient content and potential development of different plant community. Hence, such method might be considered for restoration of oligotrophic stands. Nevertheless, the period of 47 years appeared sufficient for the ground cover vegetation to recover after the WTH.Pinus sylvestris